Transforming Growth Factor β1 Genotypes in Relation to TGFβ1, Interleukin-8, and Tumor Necrosis Factor Alpha in Induced Sputum and Blood in Cystic Fibrosis - O. Eickmeier; L. v. d. Boom; F. Schreiner; M. J. Lentze; D. NGampolo; R. Schubert; S. Zielen; S. Schmitt-Grohé (Mediators of Inflammation)
Background. High-producer TGFβ1 genotypes are associated with severe lung disease in cystic fibrosis (CF), but studies combining IL-8, TNFα-, and TGFβ1(+genotype) levels and their impact on CF lung disease are scarce. Aim. Assessing the relationship between TGFβ1, IL-8, and TNF-α and lung disease in CF in an exacerbation-free interval. Methods. Twenty four patients delta F508 homozygous (median age 20.5 y, Shwachman score 75, FEV1(%) 83) and 8 controls (median age 27.5 y) were examined. TGFβ1 was assessed in serum and induced sputum (IS) by ELISA, for IL-8 and TNF-α by chemiluminescence in IS and whole blood. Genotyping was performed for TGFβ1 C−509T and T+869C utilizing RFLP. Results. TGFβ1 in IS (CF/controls median 76.5/59.1 pg/mL, P<0.074) was higher in CF. There was a negative correlation between TGFβ1 in serum and lung function (LF) (FEV1 (r=−0.488, P=0.025), MEF 25 (r=−0.425, P=0.055), and VC (r=−0.572, P=0.007)). Genotypes had no impact on TGFβ1 in IS, serum, and LF. In IS TGFβ1 correlated with IL-8 (r=0.593, P<0.007) and TNF-α (r=0.536, P<0.018) in patients colonized by bacteria with flagellin. Conclusion. TGFβ1 in serum not in IS correlates with LF. In patients colonized by bacteria with flagellin, TGFβ1 correlates with IL-8 and TNF-α in IS.